The Global Politics of Arms Sales - Pierre, Andrew J. (Book collections on Project MUSE., 2014)
Marshaling a great deal of new information in a highly readable manner, the author explains the reasons for the dramatic expansion of arms sales during the past decade and clearly traces such trends as the rise in sophistication of weapons being sold so as to include the most advanced technologies, and the shift in sales to unstable parts of the Third World. Originally published in 1982. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press.